Understanding the use of CATI and web-based data collection methods during the pandemic among digitally challenged groups at FQHCs: data from the All of Us Research Program - Kini, Soumya; Cawi, Kimberly Marie; Duluk, Dave; Yamazaki, Katrina; McQueen, Matthew B. (Frontiers in Digital Health, 2024)
Introduction The All of Us Research Program (Program) is an ongoing epidemiologic cohort study focused on collecting lifestyle, health, socioeconomic, environmental, and biological data from 1 million US-based participants. The Program has a focus on enrolling populations that are underrepresented in biomedical research (UBR). Federally Qualified Health Centers (FQHCs) are a key recruitment stream of UBR participants. The Program is digital by design where participants complete surveys via web-based platform. As many FQHC participants are not digitally ready, recruitment and retention is a challenge, requiring high-touch methods. However, high-touch methods ceased as an option in March 2020 when the Program paused in-person activities because of the pandemic. In January 2021, the Program introduced Computer Assisted Telephone Interviewing (CATI) to help participants complete surveys remotely. This paper aims to understand the association between digital readiness and mode of survey completion (CATI vs. web-based platform) by participants at FQHCs. Methods This study included 2,089 participants who completed one or more surveys via CATI and/or web-based platform between January 28, 2021 (when CATI was introduced) and January 27, 2022 (1 year since CATI introduction). Results and discussion Results show that among the 700 not-digitally ready participants, 51% used CATI; and of the 1,053 digitally ready participants, 30% used CATI for completing retention surveys. The remaining 336 participants had “Unknown/Missing” digital readiness of which, 34% used CATI. CATI allowed survey completion over the phone with a trained staff member who entered responses on the participant's behalf. Regardless of participants' digital readiness, median time to complete retention surveys was longer with CATI compared to web. CATI resulted in fewer skipped responses than the web-based platform highlighting better data completeness. These findings demonstrate the effectiveness of using CATI for improving response rates in online surveys, especially among populations that are digitally challenged. Analyses provide insights for NIH, healthcare providers, and researchers on the adoption of virtual tools for data collection, telehealth, telemedicine, or patient portals by digitally challenged groups even when in-person assistance continues to remain as an option. It also provides insights on the investment of staff time and support required for virtual administration of tools for health data collection.